2004
DOI: 10.1182/blood-2003-12-4314
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor–induced phosphorylation of the ζ chain is efficiently promoted by ZAP-70 but not Syk

Abstract: Engagement of the T-cell receptor (TCR)results IntroductionT-cell immune responses are coupled to activation of the T-cell receptor (TCR). Stimulation of this receptor results in the activation of signal transduction pathways, culminating in expression of cytokines and cellular proliferation. 1 Current models of antigen/ major histocompatibility complex (MHC)-induced T-cell activation are presented as ordered events with a sequential interaction of Src and ZAP-70/Syk protein tyrosine kinases (PTKs) with the TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 71 publications
(136 reference statements)
2
19
0
Order By: Relevance
“…5). These seemingly upstream perturbations in phosphorylation are, nevertheless, consistent with previous reports for the P116 Jurkat clone (39,40). Although Lck-mediated phosphorylation of CD3 ITAMs is widely believed to precede Zap-70 recruitment and activation (41), previous studies have revealed a synergistic role of Zap-70-mediated recruitment as well as stabilization of the interaction between Lck and CD3 at the ITAM regions independent of Zap-70 kinase activity (Fig.…”
Section: Clustering Of Phosphorylation Sites By Zap-70supporting
confidence: 92%
“…5). These seemingly upstream perturbations in phosphorylation are, nevertheless, consistent with previous reports for the P116 Jurkat clone (39,40). Although Lck-mediated phosphorylation of CD3 ITAMs is widely believed to precede Zap-70 recruitment and activation (41), previous studies have revealed a synergistic role of Zap-70-mediated recruitment as well as stabilization of the interaction between Lck and CD3 at the ITAM regions independent of Zap-70 kinase activity (Fig.…”
Section: Clustering Of Phosphorylation Sites By Zap-70supporting
confidence: 92%
“…In this regard, it is noteworthy that ZAP-70 is more effective than p72 Syk in promoting phosphorylation of TCR-z by src kinases following TCR ligation. 28 The association of ZAP-70 with Ig receptor signaling has been challenged in studies by Deglesne and colleagues, who used immobilized anti-to stimulate CLL cells in vitro and then monitored for CLL cell survival 72 hours later. They segregated patients into 2 groups, one of which had enhanced CLL cell survival with anti-(group A), and the other, which had CLL cell survival that apparently was unaffected by treatment with anti-(group B).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prior studies found that ZAP-70 could promote phosphorylation of TCR-z ITAMs in thymocytes independent of its kinase activity, serving instead as an adapter protein that could facilitate recruitment of lck to the TCR complex. 27,28 We investigated whether the kinase activity of ZAP-70 or its ability to interact with c-Cbl was required for it to enhance Ig signaling in CLL cells. For this, we transfected ZAP-70 Ϫ CLL cells with adenovirus vectors encoding ZAP-70 or well-defined mutant forms of ZAP-70 (eg, ZAP-70-KA 369 or ZAP-70-YF 292 ).…”
Section: Introductionmentioning
confidence: 99%
“…While this appears to be true for Zap70, Syk can be activated by TCR signaling even in the absence of Src family kinase activation, probably because, unlike Zap70, it can phosphorylate the ITAM directly [35][36][37]. Despite this, Zap70 has been reported to be much better than Syk at promoting phosphorylation of the TCRf chain by recruiting Lck to the signaling complex [38]. Finally, detailed examination of the roles of Syk and Zap70 in thymic development has concluded that they play distinct roles [39].…”
Section: Discussionmentioning
confidence: 99%